Unripe peach (Prunus persica) extract ameliorates damage from UV irradiation and improved collagen XVIII expression in 3D skin model. (7th December 2018) - Yonezawa, Tomoko; Momota, Ryusuke; Iwano, Hideki; Zhao, Steven; Hakozaki, Tomohiro; Soh, Chieko; Sawaki, Shigetoyo; Toyama, Kazumi; Oohashi, Toshitaka
Summary: Introduction: Collagen type XVIII regulates cellular activities of adjacent cells at the dermal‐epidermal junction (DEJ). To investigate its possible changes during aging, we compared its mRNA levels and protein localization in skin samples from female participants aged 20‐70 years old. In addition, we evaluated the beneficial effects of unripe peach extracts in a 3D skin model. Methods: Sun‐exposed or sun‐protected female skin samples were compared by DNA array or by immunohistochemistry for basement membrane components. To evaluate protective effects of fresh unripe peach extract, UV‐B irradiated human 3D skin models were incubated in the presence or absence of the extract, followed by measurements of mRNA levels by real‐time PCR, or by immunohistochemistry. Results: In aged skin samples, COL18A1 mRNA levels were lower and the protein localization exhibited less intensive signal by anti‐collagen type XVIII immunostaining. As observed in the skin tissues, collagen type XVIII exists at the DEJ in the 3D skin model. Fresh unripe peach extract significantly improved mRNA levels and partially localizations of collagen type XVIII, suggesting that fresh unripe peach extract ameliorates DEJ damages caused by UV‐B irradiation. Conclusion: Collagen type XVIII and fresh unripe peach extract can be promising protective cosmetic strategies against skin aging.